Radial carpal bone fracture in 13 dogs - Gnudi, G.; Mortellaro, C. M.; Bertoni, G.; Martini, F. M.; Cantoni, A. M.; Di Giancamillo, M.; Vignoli, M. (Veterinary and Comparative Orthopaedics and Traumatology, 2003)
The authors report 13 dogs with radiocarpal bone fracture. The lesion was bilateral in six cases and unilateral in seven. Clinical and radiographic examination of both the carpal joints was performed. One or two fracture lines, sagittal oblique and dorsal, of the radial carpal bone were detected. CT examination of two radial carpal bones helped in a better visualization of the fracture lines. A dorsal bone fragment of a fractured radial carpal bone was removed in one dog. Histopathology revealed the presence of fibro-connective tissue on the fracture surface of the bone fragment. The fibro-connective tissue did not seem to be the sequel to acute or chronic diseases, nor to any pathological healing process. The cancellous bone of the fragment was normal as was the bulk of the articular cartilage examined. A CT guided biopsy, including the sagittal oblique fracture surface of the radial carpal bone, was also performed. The specimens revealed the presence of immature cancellous bone with diffuse immature cartilage areas. The radial carpal bone has three separate centres of ossification: the primitive radial carpal bone, the central and intermediate carpal bone. The fusion of these centres occurs at 3-4 months of age. Histopathological findings suggest a possible “incomplete fusion” of the centres of ossification rather than a true fracture of the radial carpal bone or alternatively a “fatigue fracture”. A similar condition, involving the distal part of the humerus, was originally reported in several Cocker Spaniel dogs, and more recently in Rottweilers and Labrador Retrievers.
Keywords: Radial carpal bone; fracture; dog